2012
DOI: 10.2134/jeq2011.0126
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and Manure Affect Calcareous Soil and Corn Silage Nutrient Concentrations and Uptake

Abstract: Carbon‐rich biochar derived from the pyrolysis of biomass can sequester atmospheric CO2, mitigate climate change, and potentially increase crop productivity. However, research is needed to confirm the suitability and sustainability of biochar application to different soils. To an irrigated calcareous soil, we applied stockpiled dairy manure (42 Mg ha−1 dry wt) and hardwood‐derived biochar (22.4 Mg ha−1), singly and in combination with manure, along with a control, yielding four treatments. Nitrogen fertilizer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
121
3
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(143 citation statements)
references
References 57 publications
(77 reference statements)
10
121
3
9
Order By: Relevance
“…Soil tests were collected over a 2-year period to determine changes in soil fertility, total C, total N, and yield of corn silage in Idaho. Lentz and Ippolito [6] reported the only significant soil fertility increases due to biochar were in soil Mn and total organic carbon, while manure-treated soils had significant increases in extractable K, Mn, Cu, Na, and Zn when compared to the untreated control. Biochars affect on silage yield was mixed, producing a slight increase in year one but a 36 % decrease in year two [6].…”
Section: Crop Productivitymentioning
confidence: 97%
See 4 more Smart Citations
“…Soil tests were collected over a 2-year period to determine changes in soil fertility, total C, total N, and yield of corn silage in Idaho. Lentz and Ippolito [6] reported the only significant soil fertility increases due to biochar were in soil Mn and total organic carbon, while manure-treated soils had significant increases in extractable K, Mn, Cu, Na, and Zn when compared to the untreated control. Biochars affect on silage yield was mixed, producing a slight increase in year one but a 36 % decrease in year two [6].…”
Section: Crop Productivitymentioning
confidence: 97%
“…Lentz and Ippolito [6] reported the only significant soil fertility increases due to biochar were in soil Mn and total organic carbon, while manure-treated soils had significant increases in extractable K, Mn, Cu, Na, and Zn when compared to the untreated control. Biochars affect on silage yield was mixed, producing a slight increase in year one but a 36 % decrease in year two [6]. Further investigations of soil fertility showed that the hardwood biochar was unable to adjust the calcareous soil pH to improve nutrient availability and that it did not significantly improve available P, N, or any important plant cationic nutrients [6].…”
Section: Crop Productivitymentioning
confidence: 97%
See 3 more Smart Citations